1998
DOI: 10.1046/j.1365-201x.1998.0300f.x
|View full text |Cite
|
Sign up to set email alerts
|

Cation pumps in skeletal muscle: potential role in muscle fatigue.

Abstract: Two membrane bound pumps in skeletal muscle, the sarcolemma Na+-K+ adenosine triphosphatase (ATPase) and the sarcoplasmic reticulum Ca2+-ATPase, provide for the maintenance of transmembrane ionic gradients necessary for excitation and activation of the myofibrillar apparatus. The rate at which the pumps are capable of establishing ionic homeostasis depends on the maximal activity of the enzyme and the potential of the metabolic pathways for supplying adenosine triphosphate (ATP). The activity of the Ca2+-ATPas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 89 publications
0
40
0
1
Order By: Relevance
“…35 The muscular tissues are also characterized by a high ATPase activity that is required for their normal functioning. 36 Therefore, the effect of SP1017 on DNA expression in muscles may be related to this similarity between MDR tissues and muscles. We have recently observed that SP1017 significantly increases DNA uptake into MDR cells that are normally poorly transfectable with both naked DNA and DNA complexed with cationic carriers (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…35 The muscular tissues are also characterized by a high ATPase activity that is required for their normal functioning. 36 Therefore, the effect of SP1017 on DNA expression in muscles may be related to this similarity between MDR tissues and muscles. We have recently observed that SP1017 significantly increases DNA uptake into MDR cells that are normally poorly transfectable with both naked DNA and DNA complexed with cationic carriers (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
“…En la fatiga se ha observado alteración de la captación máxima de Ca 2+ por el retículo sarcoplásmico (97,110,111). El trabajo reciente de Verburg y colaboradores (112), sin embargo, sugiere que no es el aumento del Ca 2+ i basal, sino el aumento localizado del Ca 2+ cerca a la tríada asociado a cada tétanos, el factor más importante para que se produzca el desacoplamiento.…”
Section: Mecanismos Central Y Periférico De La Fatiga Muscularunclassified
“…Accumulating evidence suggests that an impairment in excitation-contraction coupling can be a primary source of force failure with severe fatigue (49); however, other sites may contribute to varying degrees (19). More specifically, the role of the sarcolemma and t-tubular membranes in conducting repetitive action potentials has been identified as a possible contributor to fatigue in humans during voluntary exercise (20,43). Failure at the level of the sarcolemma could occur because the reduction in the transmembrane gradients for Na ϩ and K ϩ during exercise reduces the ionic membrane potential.…”
mentioning
confidence: 99%